International financial market integration, asset compositions and the falling exchange rate pass-through: conference paper - Enders, Zeno; Enders, Almira; Hoffmann, Mathias (Jahrestagung des Vereins für Socialpolitik 2014, 2014)
This paper provides an explanation for the observed decline of exchange rate pass-through into import prices by modeling the effects of financial market integration on the optimal choice of the pricing currency in the context of rigid nominal goods prices. Contrary to previous literature, the interdependence of this choice with an optimal portfolio choice of internationally traded financial assets is explicitly taken into account. In particular, price setters move towards more local-currency pricing while the debt portfolio includes more foreign assets following increased financial integration. Both predictions are in line with novel empirical evidence.
Keywords: Graue Literatur; Konferenzschrift